2009
DOI: 10.1021/cm902114d
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Magnetic Properties of Ni Nanoparticles by Non-Magnetic Cores

Abstract: This work focuses on the magnetism-control study of nickel (Ni) nanoparticles (NPs) with nonmagnetic cores of noble metals (M = Ag, Au). Monodispersed M NPs used as templates were synthesized by reducing their salt with a weak reductant;oleylamine (OA). The OA acted as surfactant and non-coordinating reagent in the preparation of Ni NPs with a narrow size distribution. Then Ni atoms were controlled to grow upon the M NPs by controlling the decomposition of nickel acetylacetonate in OA. The as-prepared M and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
53
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 54 publications
2
53
1
Order By: Relevance
“…The referred data are from: solid circles, [19] solid squares, [20] solid triangles, [21] solid prism, [41] open squares, [42] open circles [43] and open triangles. [44] ChemPhysChem For large sizes of the Cu-Ag system, the Ag-rich alloys have a much broader alloying range compared to Cu-rich alloys. When the size reaches 5 nm, it is impossible for Cu-rich particles to form disordered alloys.…”
mentioning
confidence: 99%
“…The referred data are from: solid circles, [19] solid squares, [20] solid triangles, [21] solid prism, [41] open squares, [42] open circles [43] and open triangles. [44] ChemPhysChem For large sizes of the Cu-Ag system, the Ag-rich alloys have a much broader alloying range compared to Cu-rich alloys. When the size reaches 5 nm, it is impossible for Cu-rich particles to form disordered alloys.…”
mentioning
confidence: 99%
“…This could be attributed to the contribution from various anisotropies such as magnetocrystalline anisotropy, shape anisotropy, strain anisotropy and exchange anisotropy for these fine nanosized Ni in nanocomposites prepared by ball milling process. Zhang et al [46] also reported size dependent enhanced K eff of the Ni nanoparticles in the range between 1.2 × 10 4 J m −3 and 6 × 10 4 J m . High values of K eff have also been reported in other nanocrystalline system [50] prepared by mechanical alloying process.…”
Section: Resultsmentioning
confidence: 91%
“…It may be noted that the milled NiO-Al powders exhibit RTFM despite having the average size of D Ni in the range below 25 nm, which is significantly below the critical size (~34 nm) of spherical Ni particles for single domain behavior at RT [44]. Hence, Ni nanoparticles will be of single domain but prone to thermal fluctuations [45,46]. Therefore, the obtained RTFM in the presently investigated samples can be correlated to one or more of the following several origins: (i) The milled powder exhibits quite irregular morphology (see figure 4) and hence the shape anisotropy could play a key role.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to diverse structures and properties, the core-shell nanoparticles have wide applications in various fields such as surface-enhanced Raman scattering, photonic crystals, catalysis, nano-electronic devices, and biochemical sensor [1]- [7].Among the various core-shell nanoparticles, the fabrication of inorganic nanoparticles coated with the shell of polymers has attracted increasing attention as new materials because of their novel mechanical, electrical, and optical properties [8]- [9]. Characteristics of the hybrid colloids can be adjusted through the functionality of polymer moieties.…”
Section: Introductionmentioning
confidence: 99%